PERSPECTIVE OF THE RELIGIOUS FUNCTIONARIES WHO ARE THE SOURCE OF RELIGIOUS EDUCATION IN THE CONTEXT OF KORAN ABOUT WORLDLY LIFE - Kasım KOCAMAN (Fırat University, 2019)
The religious education is purported when the religion which is meant to be relation between the God and human is subjected to the education and training activities. Prophets are the original religious instructors. The religious functionaries maintained their missions all along history. They are at the same time the source and leaders of the religious education. Religions need the religious functionaries to maintain their existencies that is a sociological reality. One of the key expressions in the Koran system is the concept of “wordly life”. “Worldly life” when we consider the expressions in its context is as a result all of the materially and morally religious, political, economical, pschological, social and intellectual aspects within which human is surrendered. In this context, in the educational activities it is important to understand the attitudes, opinions, beliefs, manners and behaviours that are the source of the relations between human and the world and therefore it is also important how they are constituting in what conditions. The Koran which is the primary source of our religion is the starting point of the education and training in Islamic sense. General meanings are important in terms of understanding the Koran. In this context the Koran tries to understand and explain how the Jewish and Christian religious functionaries are in the manner against the meaning of life as well as how it is chamged and what results bring about. The Koran gives important messages to the Muslim religious functionaries how they take a stand against wordly life. The Jewish religious functionaries have been secularized and exploited and misused the religious teachings as well as changed the holy writings and they have been after religious, political, economic and social power. In order to kep their religious authorities and socip-economical statues they struggled with the God send prophets and brought about the the greatest obstacles against declaration of the religious orders and religious education and training. The concept of priesthood which is constituted by the Christian religious functionaries without observing the orders of the God led to the extremisms which has not to do wit a religious such as washinng one’s hands of everything wordly. The God almighty gives stres to this reality and cautios the believers, religious scholars and religious instructors.